The vision of the priestly narrative : its genre and hermeneutics of time - Boorer, Suzanne, 1954- (Atlanta : SBL Press, 2016)
"Boorer explores the theology of an originally independent Priestly narrative (Pg), extending through Genesis-Numbers, as a whole. In this book she describes the structure of the Priestly narrative, in particular its coherent sequential and parallel patterns. Boorer argues that at every point in the narrative's sequential and parallel structure, it reshapes past traditions, synthesizing these with contemporary and unique elements into future visions, in a way that is akin to the timelessness of liturgical texts. The book sheds new light on what this material might have sought to accomplish as a whole, and how it might have functioned for, its original audience.
Cover; Contents; Acknowledgements; Abbreviations; Introduction; The Structure of Pg; The Genre and Hermeneutics of Pg; The Paradigmatic Nature of the Scenarios within Pg's Story of the Nation and their Hermeneutics of Time ; The Interpretation of the Story of the Nation with Pg as a Whole, Its Trajectory, and Parallels, in Light of its Hermeneutics of Time ; Conclusion: Embodying the World of the Text, Cognitively, Existentially, and through Ritual Praxis, or Not ; Bibliography; Index of Biblical References; Index of Modern Authors
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: P document (Biblical criticism); Bible. -- Criticism, interpretation, etc; RELIGION / Biblical Studies / Old Testament; Electronic books